KAJIAN PENGARUH JENIS PENGERING DAN KONSENTRASI MALTODEKSTRIN TERHADAP PRODUK MINUMAN TEH - SECANG EFFERVESCENT: (Study Effect Dryer and Concentration of Maltodextrin to Drink Tea Products–Sappan Wood Effervescent) - Mulyati M. Tahir; Jumriah Langkong; Abu Bakar Tawali; Nurlaila Abdullah; Surahman Surahman (Hasanuddin University Food Science and Technology Study Program, 2019)
Tea and sappanwood have long been believed to have health benefits for human body. The content of antioxidants were able to scavange free radicals. To combine the attributes of the product in the preparation (instant), sparkle taste, and have health benefits. This effervescent beverage is prepare to combine of bioactive components in tea and sappanwood so it will produce health tea-sappanwood beverage. The purpose of this study was to determine the best concentration of maltodextrin and the right type dryer in making of tea-sappanwood effervescent. The research method was Completely Randomized Design (CRD) with two factors. Factor I was the concentration of the maltodextrin consists of 6 levels (5%, 8%, 11%, 14%, 17%, and 20%). Factor II was a type of dryer consisting of 2 levels (vacuum and freeze dryer). The analysis performed include moisture content, pH, antioxidant activity, and the organoleptic properties against color, flavor, and taste. The results showed that the best concentration was using maltodextrin concentration of 17%-20% It had a moisture content of 1.99%, pH of 6.16, antioxidant activity of 85.73% the results of the organoleptic properties (colour, flavor, and taste) favored by panelists. On the other hand, freeze dryer was the best dryer method. Result analysis of moisture content, pH, and antioxidant activity were 2.24%, 6.28, 82.49% respectively and the organoleptic properties (colour, flavor, and taste) are favored by panelists.